Advancing safety in chemical industries: A systematic review of risk mitigation strategies and technologies - S, Sothivanan.; K, Manikandan.; E, Nakkeeran. (Edelweiss Applied Science and Technology, 2025)
The review provides a comprehensive analysis of the assessment of risk assessment and hazard identification methodologies, the role of safety culture, and training programs in the chemical industry. This multi-faceted approach to risk management ensures the safety of workers and the environment. The PRISMA guidelines consist of article identification, screening, and eligibility assessment. Here, we focus on a systematic review of risk mitigation strategies and technologies, which are vital for ensuring safety and compliance with regulations. However, qualitative risk assessment methods are evaluated, emphasizing the benefits of integrating both approaches for a comprehensive understanding of risks and hazards. The exploration of emerging cutting-edge technologies, including automation, robotics, and AI, shows great potential in enhancing risk assessment and hazard identification processes. These technologies enable real-time monitoring, early detection of potential hazards, and improved risk assessment accuracy. It also acknowledges the difficulties with data quality, algorithm transparency, and human-machine interaction. Additionally, it suggests to policymakers and experts in the chemical sector how they can improve their risk management tactics, make workplaces safer, and lower the frequency of accidents and hazardous situations. Significantly, this study recommends that future studies focus on creating uniform frameworks and policies to simplify risk mitigation procedures.